Applications of leech therapy in medicine: a systematic review - Hosseini, Mahsa; Jadidi, Ali; Derakhshan Barjoei, Mohammad Moein; Salehi, Mehdi (Frontiers in Medicine, 2024)
Background Leech therapy (LT) is one of the most widely used treatment methods in traditional medicine. The present study aimed to systematically review clinical trials regarding the effects of LT on the prevention and healing of different diseases. Methods To identify all relevant published studies, we conducted a comprehensive search of PubMed, Scopus, and Web of Science databases without any temporal or geographical constraints until April 2023. To categorize the articles, five stages were considered. The PRISMA checklist and Cochran’s bias analysis tool were used. Results In total, 12 trials that met the inclusion criteria were studied. The results of the studies showed that LT has had successful outcomes in treating different conditions. These included hormonal and metabolic complications, cardiovascular problems, and inflammatory-based diseases. Conclusion “Leech therapy” is a traditional medical treatment used successfully to control and treat various conditions. Although this method can have complications, it is possible to benefit from this low-cost and low-complication treatment by taking preventive measures.